Analisis rasio IFNy - IL 4 pada berbagai kelompok Nefritis Lupus - Handono, Kusworini (Lembaga Penelitian Universitas YARSI, 2009)
Lupus Nephritis (LN) is a serious manifestation of Systemic Lupus Erythematosus (SLE), that is classified into 6 different classes according to WHO criteria. It has been shown that histological pattern of LN varied significantly among the class and the etiology of the difference in the histological phenotypes remains unknown to date. Several studies indicatedassociation between Th1/Th2 cytokines balance with genetic factor. The present study aims to evaluate the interferron-? (IFNy) / interleukin 4 (IL4) ratio among different histologicalphenotype of LN patients in Indonesia. The study was conducted in 40 female SLE patients at Dr. Saiful Anwar Hospital, Malang, Indonesia. Histologic phenotypes classification was based on WHO criteria (1995). The serum level of IFNy and IL4 was assayed using ELISA and the association between IFNy-IL4 ratio with the histological phenotypes was statistically analyzed using ANOVA. The study revealed that among 31 SLE subjects undergone renal biopsy, class I/II, class III/IV and class V were observed in 13, 12 and 6 subjects respectively. The IFNy-IL4 ratio in class III/IV subjects was significantly higher compared to those in the other classes (p<0.000). However, the IL4 in the class III/IV was significantly lower than the other classes. The findings indicated that the activity of the Th1 immune response tend to be higher in class III/IV LN patients whereas in class V LN patients, the Th2 response prevail. In conclusion, the study indicated that the IFNy-IL4 cytokine ratio might influence the pathogenesis of LN.